PRODUCTIVE ZAKAT EMPOWERMENT WITH THE STYLE OF A ZAKAT VILLAGE - Emi Yasir; Muhammad Yasir (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2024)
Productive zakat is currently a growing trend among the people of Aceh. Zakat is also a social activity that can be a solution to the current poverty. Previous studies in several places regarding productive zakat empowerment were still not optimal due to several obstacles that had to be addressed. This study aims to determine the implementation and implementation of productive zakat empowerment with the village zakat model in Aceh Besar District. This research uses a qualitative approach with descriptive methods. The data was collected by interviewing using purposive sampling technique. Samples taken are Mustahiq, Baitul Mal Institute, and Islamic Sharia Service. The empowerment of productive zakat is measured using three indicators of zakat distribution, village feasibility, and business results from productive zakat. Based on the results of this study, productive zakat with the village-based zakat model is a positive activity that can lead to an independent attitude for the community in managing businesses and improving the welfare of the less fortunate and increasing their standard of living.